The effect of excitation frequency on the flow structure of a plane jet subject to acoustic excitation using particle image velocimetry - Kumar, Sanjay; Murugan, Sudharson; Brohi, Ali Anwar; Ahmed, Zaheer (Physics of fluids (1994), 2025)
The flow field of plane jets has been studied experimentally under both no-excitation and excitation conditions. The jet pulsation intensity and jet Reynolds number were fixed at 1.0 and 500, respectively, while the excitation frequency increased gradually from 40, 60, and 100 Hz. Acoustic excitation characteristics were determined using hotwire anemometry. Laser-assisted smoke flow visualization techniques were used to render flow features, and an edge detection technique was employed to quantify jet spreading characteristics. The velocity fields were measured using particle image velocimetry. The results show that the velocity pulsation near jet exits exhibited hump-like periodic oscillation signals. Kármán vortex street is generated periodically downstream of plane jet on flow in natural jet flow. These instabilities are replaced with mushroom-shaped coherent vortex structure when jet is under excitation. Higher excitation frequencies intensified these mushroom-shaped structures, which then became puff-like structures and eventually led to vortex breakdown resulting in turbulence eddies. Lagrangian integral time scales and length scales attribute strong vortex stretching effect to vortices breakup phenomenon, which was strong in near field in cases of excitation. In addition, small-length scales of fine turbulence eddies confirmed cascade of turbulent kinetic energy. Flow pulsation magnifies jet spread and vortex's strength. The streamline patterns revealed a two-counter rotating vortex structure in outer shear layers of plane jet flow. Turbulence intensities were significantly higher in near field due to the rapid roll-up of vortices and strong entrainment effect, leading to a higher momentum exchange rate and prominent mixing enhancement significantly during excitation.